Bibliometric Analysis of Biotechnology Development - Judijanto, Loso; Auliani, Restu (West Science Nature and Technology, 2024)
This study utilizes bibliometric analysis to explore the landscape of biotechnology research from a comprehensive perspective, focusing on thematic clusters, research trends, research opportunities, and author collaboration networks. Through a series of visualizations created using VOSviewer, we identify four major thematic clusters: industrial applications, agricultural biotechnology, biotechnological processes, and commercial development. Our temporal analysis traces the progression from foundational research towards advanced applications and industry integration, occurring over the last two decades. The research opportunities identified include expanding studies in underrepresented areas like microalgae, biodiversity, and innovative biotechnological tools. Additionally, our analysis of author collaborations reveals diverse patterns, ranging from tight-knit groups to independent researchers, indicating varied collaborative dynamics. The findings provide a nuanced understanding of the evolution, current state, and emerging trends within biotechnology, offering valuable insights for future research directions and strategic industry applications.